2013
DOI: 10.4137/bcbcr.s11215
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Ultrasound for Breast Cancer Staging: an Attempt to Identify Clinical/Histopathological Factors Impacting Diagnostic Performance

Abstract: Aim:To assess the diagnostic value of pre-surgery axillary ultrasound for nodal staging in patients with primary breast cancer and to identify clinical/histopathological factors impacting diagnostic performance.Study design:Single-center, retrospective chart analysis. We assessed sensitivity, specificity, and positive and negative predictive value of clinical examination as well as axillary ultrasound vs. clinical examination alone. The histopathological results were the standard of truth. In addition, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
(35 reference statements)
4
10
2
Order By: Relevance
“…Moreover, PAUS-positive patients have more macrometastases and more lymph nodes involved than those who have metastases identified by SLNB alone. These results are consistent with those of Wely et al [11] and others [12,13], who also showed that patients with ultrasound-positive lymph nodes often have more extensive lymph node involvement and unfavourable disease characteristics. In particular, in their consideration of the impact of the Z0011 trial, Verheuvel et al found that the PAUS-positive group also had unfavourable disease characteristics and a worse prognosis than SLNB positive pa-tients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, PAUS-positive patients have more macrometastases and more lymph nodes involved than those who have metastases identified by SLNB alone. These results are consistent with those of Wely et al [11] and others [12,13], who also showed that patients with ultrasound-positive lymph nodes often have more extensive lymph node involvement and unfavourable disease characteristics. In particular, in their consideration of the impact of the Z0011 trial, Verheuvel et al found that the PAUS-positive group also had unfavourable disease characteristics and a worse prognosis than SLNB positive pa-tients.…”
Section: Discussionsupporting
confidence: 92%
“…It is likely to have been due to the lymph node burden resulting in marked morphological changes in the involved nodes that were readily detected by the radiologist at the time of presentation. These findings are consistent with those of Wely et al [11] and Ertan et al [12], who also showed that patients with ultrasoundpositive lymph nodes often have more extensive lymph node involvement. The overall PAUS positive detection rate in our unit was 50.5%.…”
Section: Discussionsupporting
confidence: 92%
“…AUS is a basic and initial diagnostic tool used for patients with breast cancer [ 70 , 71 ]. Although the ability of AUS to provide high-quality images has gradually improved, the appearance of ALNs with normal-appearing morphology ranges between 26% and 52% [ 8 , 11 , 59 , 72 , 73 , 74 , 75 ]. The diagnostic accuracy of AUS can be affected by various factors, including the operator’s skill and experience and the ultrasound equipment used.…”
Section: Discussionmentioning
confidence: 99%
“…The positive predictive value for nodal metastases was reported as 93.1% for nodal ultrasound with core biopsy in a retrospective study of 662 patients with newly suspected breast cancer [14]. It has been suggested that the absence of a fatty hilum on imaging be an indicator for performing biopsy [17, 18]. …”
Section: Discussionmentioning
confidence: 99%